Effect of B complex vitamins on life quality and neuropathic pain intensity in patients undergoing hemodialysis - Forni, José Eduardo Nogueira; Ana Carolina Rodrigues; Amanda Fidalgo Lima; Bianca de Oliveira Lemos; Beatriz Arid Rudnick; Gabriela Modulo Molina; Narayana Silva Paiva (Asian Journal of Medical Sciences, 2022)
Background: Neuropathic pain (NP) is characterized by chronic pain with a generally strong intensity that leads to limitations regarding activities of daily living. Aims and Objectives: The aim of the study was to investigate the effect of B complex vitamins on NP intensity and life quality in patients undergoing hemodialysis. Materials and Methods: A randomized controlled double-blind clinical trial was conducted among hemodialysis patients with clinical diagnosis of NP randomly allocated to two groups: A (gabapentin) and B (B vitamins). DN4, visual analog scale, and Kidney Disease Quality of Life-Short Form questionnaire were used to identify NP, measure pain intensity, and assess quality of life, respectively. Results: A significant reduction in pain occurred after treatment with gabapentin (P=0.003). In the B group, the reduction of pain went from a mean of 7.27 to 5.09 after treatment (P=0.056). In the A group, a significantly poorer quality of life was reported after treatment in the social relations domain (P=0.010). A significant improvement in quality of life and environment domains (P=0.025 and 0.049, respectively) was reported after use of B vitamins. Conclusion: These findings demonstrate that B complex vitamins for the treatment of NP in hemodialysis patients should be investigated further, as this form of treatment contributed to a reduction in pain intensity and suffering with no side effects and at low cost.